Undergraduates' organizational citizenship behavior and academic dishonesty / Shaiful Annuar Khalid, Norshimah Abdul Rahman and Abdul Rashid Sinthamadar - Khalid, Shaiful Annuar; Abdul Rahman, Norshimah; Sinthamadar, Abdul Rashid (Universiti Teknologi MARA, Perlis, 2012)
Academic dishonesty such as cheating and plagiarism are manifestations of the desire to get good grades among students. This problem is becoming one of the important issues at all university campuses. This study looks at the impact of organizational citizenship behavior on students' academic dishonesty. The data were taken from 217 undergraduate business and accounting students from a public university of Peninsular Malaysia. The findings of this study revealed that academic cheating is not a serious problem among students. Furthermore, OCB dimensions of helping behavior, conscientiousness, sportsmanship and courtesy were significantly and negatively associated with academic dishonesty.